Perbandingan Reaksi Pasar pada Perusahaan LQ45 dan Non LQ45 atas Pengumuman Stock Split - Wahyudi, Kadek; Putra, I Nyoman Wijana Asmara (E-Jurnal Akuntansi; Vol 30 No 2 (2020)DO - 10.24843/EJA.2020.v30.i02.p03, 2020)
Stock split announcements are believed to cause investor reaction. The LQ45 Index company that already has high liquidity in IDX is a stock split. This research aims to test the difference of the company's market reaction LQ45 before and after the stock split announcement, test the reaction difference of the non-LQ45 company market before and after the stock split announcement, and test the market reaction difference between LQ45 and non LQ45 companies on the stock split announcement. This research sample is a company that does stock split up during January 2007-July 2019. Market reactions are measured by abnormal return. The analytical techniques used are different tests. The results showed there was a reaction of the company's market LQ45 and non LQ45 on the stock split announcement, and there was a difference in market reaction between LQ45 and non-LQ45 companies over stock split announcements. Keywords: Stock Split; Abnormal Return Difference; Market Reaction.